CORRUPTION IN FRANCE - Georgieva Hadži Krsteski, Natasha (Journal of process management and new technologies, 2016)
In accordance with the research conducted by Transparency International, in the period from 2009 until 2012, it is found that this European country did not undergo drastic changes during this period, when it comes to its ranking. According to this research, France belongs to the countries that undertake appropriate measures for the fight against corruption – and it is at a satisfactory level in modern conditions, even in well-developed countries. Corruption in France rests on three major authorities: the Financial Intelligence Unit, the Central Service for the Prevention of Corruption (SCPC) and the Central Brigade for the Fight against Corruption (BCLC). As a result of the good institutional cooperation, France is prepared to prevent corruption in the state authorities. The international community disposes of data that refer to the detrimental and difficult consequences caused by corruption. Such findings led to two key issues – prevention of corruption and fight against corruption, not only in France, but in other countries as well. In order to overcome this large-scale problem, many international documents have been adopted, ratified by the Republic of Macedonia.